A Comparison of Age, Size, and Fecundity of Harvested and Reference White Sucker Populations. (4th April 2017) - Begley, Meg; Coghlan, Stephen M.; Zydlewski, Joseph
Abstract: White Suckers Catostomus commersonii are an important source of fresh bait for the Maine lobster fishery. The Maine Department of Inland Fisheries and Wildlife began issuing commercial harvest permits in 1991, without reporting requirements or limits on the number of permits. There is recent concern that overfishing may be occurring. To infer impact, we investigated demographic differences between White Sucker populations in lakes open to harvest and those in lakes closed to harvest. Each of three harvested lakes was paired to a nearby closed lake as a reference based on general size, morphometry, and information on harvest pressure. In total, 976 spawning White Suckers were collected from the six lakes in 2014 (120–282 individuals/lake). Fish size, estimated age, fecundity, and mortality rates were compared between lakes. We hypothesized that we would find smaller, younger, and less‐fecund individuals in harvested lakes compared to reference lakes. Size and age distributions for both sexes differed between nearly all lake pairs (except between males from one pair). White Suckers from reference lakes were larger and older and had greater gonadosomatic indices and fecundity than fish from harvested lakes. Estimated annual mortality rates were at least twofold higher in harvested lakes than in reference lakes. We detected some differences in von Bertalanffy growth parameters between lake pairs, as might occur under selective harvest pressure. The growth coefficient was smaller for reference lakes than for harvested lakes, while asymptotic length was greater for reference lakes than for harvested lakes. The data suggest that current levels of exploitation are resulting in greater age truncation in existing White Sucker populations. Received September 27, 2016; accepted January 24, 2017 Published online April 4, 2017